2020
DOI: 10.2147/ndt.s216389
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inflammation and Coronary Heart Disease Risk in Patients with Depression in China Mainland: A Cross-Sectional Study</p>

Abstract: The risk of coronary heart disease (CHD) in patients with major depressive disorder (MDD) is higher than that in the general population. However, the mechanisms underlying the increased CHD risk in patients with MDD remain unclear. Inflammation plays an important role in the pathogenesis of MDD and CHD. Therefore, we explored the relationship between inflammatory biomarkers and CHD risk in patients with MDD. Methods: We included 454 patients with acute MDD and 458 controls that matched the sample in age and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
2
27
0
2
Order By: Relevance
“…Higher levels have been associated with worse prognosis in several medical diseases, in particular in the field of oncology. In a single study, higher SII levels were associated with major depressive disorder (MDD) ( Zhou et al, 2020 ), suggesting that it could be a marker of the low-grade inflammation observed in mood disorders ( Benedetti et al, 2020 , Arteaga-Henríquez et al, 2019 ). Interestingly, we also found a direct correlation between OCI and MLR and a trend for a direct correlation between OCI and NLR and SII, suggesting that higher baseline inflammation could be associated whit later OC symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels have been associated with worse prognosis in several medical diseases, in particular in the field of oncology. In a single study, higher SII levels were associated with major depressive disorder (MDD) ( Zhou et al, 2020 ), suggesting that it could be a marker of the low-grade inflammation observed in mood disorders ( Benedetti et al, 2020 , Arteaga-Henríquez et al, 2019 ). Interestingly, we also found a direct correlation between OCI and MLR and a trend for a direct correlation between OCI and NLR and SII, suggesting that higher baseline inflammation could be associated whit later OC symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…NLR, MLR and SII are low-cost, suitable for clinical routine analysis, and reproducible markers of the systemic inflammatory response, which can be easily derived from blood cell essay and determined under simple laboratory conditions ( Balta et al, 2013 ). Several studies have proven that these inflammatory ratios can be used as inflammatory biomarkers in depression ( Mazza et al, 2018 , Wang et al, 2021 , Zhou et al, 2020b ). In the present study, we have found that baseline SII predicted severity of depressive psychopathology and neurocognitive performance at the three-months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2021) found that high SII index levels are associated with unipolar depression in male diabetic patients [44]. Also, Zhou et al (2020) reported that MDD patients have an increased SII index compared with healthy controls [45]. A recent study showed that the degree of reduction of SII index between admission and discharge predicted the remission of depression in Coronavirus Disease (COVID) 19 survivors [46].…”
Section: Introductionmentioning
confidence: 99%